2000
DOI: 10.1023/a:1007173722426
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have immunohistochemically examined the distribution of the H antigens of type 1, type 2 and type 3/4 chains of the ABO(H) histo-blood group system in human normal colon and in colon cancer using three monoclonal antibodies specific for each of the H type 1/2, H type 2, and the H type 3/4 chain. We unexpectedly found that mucosa of the normal colon from secretors but not that from nonsecretors expressed only H type 1 and did not express H type 2 or H type 3/4. The H type 1 was expressed in goblet cells. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…We have also observed that blood group antigen H types 2 and 3 were more abundant than H type 1 antigen in CRC cell lines. Similarly, antibody staining studies showed region-specific expression of mainly H type 1 blood group antigen H in healthy colon tissue, in contrast to colon cancer tissues aberrantly expressing blood group antigens H type 2 and 3 associated with tumour progression in the distal colon and rectum [36].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We have also observed that blood group antigen H types 2 and 3 were more abundant than H type 1 antigen in CRC cell lines. Similarly, antibody staining studies showed region-specific expression of mainly H type 1 blood group antigen H in healthy colon tissue, in contrast to colon cancer tissues aberrantly expressing blood group antigens H type 2 and 3 associated with tumour progression in the distal colon and rectum [36].…”
Section: Discussionmentioning
confidence: 90%
“…Apart from the erythrocytes, the ABH antigens can be expressed also in the gastrointestinal tract and secretions, where the Se-FUT enzyme (FUT2) is responsible for their biosynthesis [35]. However, several reports have demonstrated the expression of blood group ABH antigens in colon cancers from non-secretors with inactive enzyme [36,37]. Cell lines showing expression of blood group H antigens such as CaCo-2, HCT15, HCT8, SW948, SW1116, and SW837 were derived from tumours of blood group O secretor positive individuals [38].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we hypothesized that the ABO blood group antigens, which are expressed on the intestinal mucosa of secretor individuals [16,17] determine the gastrointestinal microbiota composition in healthy individuals. We recruited 79 healthy adult volunteers living in Southern Finland to test this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Krusius et al reported that ABO blood group antigens are present on erythrocyte glycoproteins as polyglycosyl chains [24]. Studies focusing on the expression of glycans in the human intestine have identified the presence of ABO type 1 glycans in the mucosal layer covering human orogastrointestinal tract and have shown that the fucosylated glycans, including ABO blood group glycan antigens, are detected less abundantly towards the distal parts of the intestine [16,17]. The ABO blood group glycans are reported to be exported to the mucus layer from goblet cells residing in the crypts of the small intestine [17].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the expression of H type 1 carbohydrates in the normal colon is under the control of FUT2 gene-encoded fucosyltransferase. However the aberrant expressions of H type 2 and H type 3/4 carbohydrates in colon cancer tissues of secretors is regulated by the same enzyme 57 . The reasons underlying these changes have not been clarified.…”
Section: Introductionmentioning
confidence: 99%